2015
DOI: 10.18632/oncotarget.5064
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin, a phytochemical, potentiates sorafenib-induced apoptosis and abrogates tumor growth in athymic nude mice implanted with BRAF-mutated melanoma cells

Abstract: Melanoma is the most deadly form of cutaneous malignancy, and its incidence rates are rising worldwide. In melanoma, constitutive activation of the BRAF/MEK/ERK (MAPK) and PI3K/AKT/mTOR (PI3K) signaling pathways plays a pivotal role in cell proliferation, survival and tumorigenesis. A combination of compounds that lead to an optimal blockade of these critical signaling pathways may provide an effective strategy for prevention and treatment of melanoma. The phytochemical fisetin is known to possess anti-prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 55 publications
4
51
0
Order By: Relevance
“…In vitro studies using A375 and SK-MEL-28 demonstrated that fisetin combined with sorafenib decreased invasion, migration, pMEK1/2, pERK1/2, PI3K activation (p110α), pAKT, and pmTOR while increasing PTEN. These results were confirmed in athymic nude mice [189]. Combination treatment using sorafenib and fisetin vigorously repressed migration, invasion, and expression of MMP-2 and MMP-9 compared with monotherapy.…”
Section: Combination Treatments May Effectively Inhibit Melanoma Emtmentioning
confidence: 70%
“…In vitro studies using A375 and SK-MEL-28 demonstrated that fisetin combined with sorafenib decreased invasion, migration, pMEK1/2, pERK1/2, PI3K activation (p110α), pAKT, and pmTOR while increasing PTEN. These results were confirmed in athymic nude mice [189]. Combination treatment using sorafenib and fisetin vigorously repressed migration, invasion, and expression of MMP-2 and MMP-9 compared with monotherapy.…”
Section: Combination Treatments May Effectively Inhibit Melanoma Emtmentioning
confidence: 70%
“…It was assumed that CDC25C plays a role in the regulation of the CDK1/cyclin B complex for cell cycle progression . It was also reported that fisetin induced G2/M phase arrest in A431 epidermoid carcinoma cells . Results also showed that fisetin promoted the expression of Chk1 and ‐2 in SCC‐4 cells in time‐dependent manners.…”
Section: Discussionmentioning
confidence: 96%
“…It was demonstrated that melatonin potentiated the effect of fisetin in melanoma cells by activating cytochrome c-dependent apoptosis and inhibiting COX-2/iNOS and NF-κB/p300 signaling pathways [83]. Combination of fisetin and the BRAF inhibitor sorafenib was found to be extremely effective in inhibiting the growth of BRAF-mutated human melanoma cells resulting in enhanced apoptosis, reflected by cleavage of caspase-3 and PARP, increased expression of Bax and Bak, and inhibition of Bcl-2 and Mcl-1 [84]. In addition, synergistic effect of fisetin and sorafenib was observed in human cervical cancer HeLa cells, where i n vitro and in vivo studies revealed that the combination was clearly superior to sorafenib treatment alone.…”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 99%